Cinema by design : art nouveau, modernism, and film history - Fischer, Lucy (New York, NY : Columbia University Press, 2017)
Art Nouveau thrived from the late 1890s through the First World War. The international design movement reveled in curvilinear forms and both playful and macabre visions and had a deep impact on cinematic art direction, costuming, gender representation, genre, and theme. Though historians have long dismissed Art Nouveau as a decadent cultural mode, its tremendous afterlife in cinema proves otherwise. In Cinema by Design, Lucy Fischer traces Art Nouveau's long history in films from various decades and global locales, appreciating the movement's enduring avant-garde aesthetics and dynamic ideology. Fischer begins with the portrayal of women and nature in the magical "trick films" of the Spanish director Segundo de Chomon; the elite dress and decor design choices in Cecil B. DeMille's The Affairs of Anatol (1921); and the mise-en-sc ne of fantasy in Raoul Walsh's The Thief of Bagdad (1924). Reading Salome (1923), Fischer shows how the cinema offered an engaging frame for adapting the risque works of Oscar Wilde and Aubrey Beardsley.
Introduction -- Art Nouveau and the age of attractions -- Art nouveau and American film of the 1920s: prestige, class, fantasy, and the exotic -- Architecture and the city: Barcelona, Gaudí, and the cinematic imaginary -- Art nouveau, chambers of horror, and "the Jew in the text" -- Art nouveau, patrimony, and the art world -- Epilogue: the 1960s and the Art nouveau revival.
Print version record.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Art nouveau; Decoration and ornament -- Art nouveau; Art in motion pictures; Art nouveau; Décoration et ornement -- Art nouveau; Art au cinéma.; Art Nouveau; ART -- History -- Modern (late 19th Century to 1945); Art in motion pictures; Art nouveau; Decoration and ornament -- Art nouveau